Sclerotherapy for oral hemangioma - Navadeepak Korvipati; Kotya Naik Maloth; Sunitha Kesidi; Shefali Waghray (Wolters Kluwer Medknow Publications, 2016)
Hemangiomas are well-known benign neoplasms of the body most commonly occurring in the head and neck region and less commonly in the oral cavity. The predominant site of occurrence, in the oral cavity, is lips followed by gingiva, tongue and palate. Treatment is primarily dependent on correct diagnosis of the lesion and its anatomic location. Here, we report a case of hemangioma on posterior third of the tongue in 34-year-old male patient, who was treated by sclerotherapy with sodium tetradecylsulphate (setrol) sclerosing agent.